Monitoring system of sustainable development in the European Union - Urbaniec, Maria (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
Sustainable Development Indicators are the main tool for monitoring of the EU Sustainable Development Strategy. The aim of this paper is to indicate strategic conditions for monitoring sustainable development as well as to evaluate the current system of indicators for monitoring of the EU Sustainable Development Strategy. This paper presents also a synthetic assessment of the progress of sustainable development in the European Union on the basis of headline indicators. Based on the statistical results, a positive trend can only be observed in the case of headline indicators related to following themes of the SDI framework "demographic change" and "climate change and energy", while the lack of significant improvement in the direction of more sustainable development shows the headline indicator in the field "social inclusion" . Monitoring methodology and continuous updating of data collection at EU level creates new challenges for the development of new indicators. The results indicate the need for further improvement of the measurement and control of the action for sustainable development.